Aminoguanidines: New leads for treatment of Giardia duodenalis infection. (August 2019) - Abraham, Rebecca J.; Abraham, Sam; Stevens, Andrew J.; Page, Stephen W.; McCluskey, Adam; Trott, Darren J.; O'Handley, Ryan M.
Abstract: Giardia duodenalis is an ubiquitous parasitic pathogen that causes significant morbidity and mortality worldwide. Failures in drug therapy are commonly due to poor patient compliance as a result of the need for repeated administration, off target drug effects and increasing parasite drug resistance. In this study the in vitro efficacy and selectivity of the aminoguanidine compound robenidine and 2 structural analogues against Giardia were determined. After 5 h exposure to each compound the IC50 was as low as 0.2 μM with corresponding MLCs as low as 2.8 μM. This is in contrast to metronidazole which required 24 h to exhibit inhibitory activity. A modified adherence assay, developed for this study, demonstrated that three of the compounds inhibited in vitro adherence of the parasite. The lead compound exhibited rapid giardicidal activity (<5hr). In addition, microscopy studies demonstrated damage to the plasma membrane of trophozoites. In conclusion, a class of aminoguanidines, represented by robenidine, has shown antigiardial activity warranting further investigation. Graphical abstract: Image 1 Highlights: Robenidine has faster antigiardial activity in vitro compared to metronidazole. Novel structures developed with improved antigiardial activity compared to robenidine. Giardia is unable to recover after short exposure times to novel antigiardials Electron microscopy images show detailed structural damage after robenidine exposure.